Influence of Musical Enculturation on Brain Responses to Metric Deviants - Haumann, Niels T.; Vuust, Peter; Bertelsen, Freja; Garza-Villarreal, Eduardo A. (Frontiers in Neuroscience, 2018)
The ability to recognize metric accents is fundamental in both music and language perception. It has been suggested that music listeners prefer rhythms that follow simple binary meters, which are common in Western music. This means that listeners expect odd-numbered beats to be strong and even-numbered beats to be weak. In support of this, studies have shown that listeners exposed to Western music show stronger novelty and incongruity related P3 and irregularity detection related mismatch negativity (MMN) brain responses to attenuated odd- than attenuated even-numbered metric positions. Furthermore, behavioral evidence suggests that music listeners’ preferences can be changed by long-term exposure to non-Western rhythms and meters, e.g. by listening to African or Balkan music. In our study, we investigated whether it might be possible to measure effects of music enculturation on neural responses to attenuated tones on specific metric positions. We compared the magnetic mismatch negativity (MMNm) to attenuated beats in a ‘Western group’ of listeners (n=12) mainly exposed to Western music and a ‘Bicultural group’ of listeners (n=13) exposed for at least one year to both Sub-Saharan African music in addition to Western music. We found that in the ‘Western group’ the MMNm was higher in amplitude to deviant tones on odd compared to even metric positions, but not in the ‘Bicultural group’. In support of this finding, there was also a trend of the ‘Western group’ to rate omitted beats as more surprising on odd than even metric positions, whereas the ‘Bicultural group’ seemed to discriminate less between metric positions in terms of surprise ratings. Also, we observed that the overall latency of the MMNm was significantly shorter in the Bicultural group compared to the Western group. These effects were not biased by possible differences in rhythm perception ability or music training, measured with the Musical Ear Test. Furthermore, source localization analyses suggest that auditory, inferior temporal, sensory-motor, superior frontal, and parahippocampal regions might be involved in eliciting the MMNm to the metric deviants. These findings suggest that effects of music enculturation can be measured on MMNm responses to attenuated tones on specific metric positions.